(3fHPI JJYdb HecI GdeTQaI hGdeOjfI GdefhQI hHjJ GdebOSs - (3CHi GdYHGS TgGH GdOjf CMeO Hf CMeO Hf SdGeI GdbdjhHi GdTGaYjs ((3eMeO Hf CMeO Hf CHj GdYHGS CMeO Hf eMeO GdRHjQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ai CMSf Jbhje CeG HYO agPg fHPI dWjaI eTJedI Ydi eHGMK TQjaI dGjSJZfi Yf eYQaJgG GdaGVd GdHGH GdChd ajeG jJYdb HGdHjJ GdTQja s
(3BNQgG (B:s
(3hai GdNHQ LHQGf HjJ GdebOS LjQGf Gddg hGddg dGjYPH LjQGfg CHOqG hef UHQ Ydi Scfi HdOI SfI BJGg Gddg HQRbI hGdMeO ddg hgPG BNQ eG CQOfG EjQGOg s
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhds
(3fSNI fbdJ ef fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs